2012
DOI: 10.6064/2012/635431
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response and Pathogenicity of the Necrotrophic Fungal PathogenAlternaria alternata

Abstract: The production of host-selective toxins by the necrotrophic fungus Alternaria alternata is essential for the pathogenesis. A. alternata infection in citrus leaves induces rapid lipid peroxidation, accumulation of hydrogen peroxide (H2O2), and cell death. The mechanisms by which A. alternata avoids killing by reactive oxygen species (ROS) after invasion have begun to be elucidated. The ability to coordinate of signaling pathways is essential for the detoxification of cellular stresses induced by ROS and for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 211 publications
(215 reference statements)
3
64
0
1
Order By: Relevance
“…Fungal strains lacking NPS6, YAP1, HOG1, SKN7, or NOX all show increased sensitivity to ROS and reduced virulence in citrus. Thus we conclude that the reduced virulence of the mutants is likely attributable to their inability to deal with toxic ROS in planta (Chung, 2012). Our results support the important role of ROS detoxification during A. alternata pathogenesis in citrus.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Fungal strains lacking NPS6, YAP1, HOG1, SKN7, or NOX all show increased sensitivity to ROS and reduced virulence in citrus. Thus we conclude that the reduced virulence of the mutants is likely attributable to their inability to deal with toxic ROS in planta (Chung, 2012). Our results support the important role of ROS detoxification during A. alternata pathogenesis in citrus.…”
Section: Discussionsupporting
confidence: 79%
“…Although the early stages of Alternaria brown spot in citrus require the production of host-selective toxin, our previous studies showed that the colonization of A. alternata in its host plants relies also on the ability to detoxify reactive oxygen species (ROS) Chung, 2012). During the course of host colonization, fungal pathogens of plants often need to overcome an oxidative burst resulting from the production and accumulation of highly toxic ROS (Apel & Hirt, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…S8). The increased fungal colonization may have resulted from the high levels of extracellular ROS, which were reported to be important for the development and pathogenicity of some necrotrophic pathogens, such as Botrytis cinerea, Sclerotinia sclerotiorum, and Alternaria alternate (Govrin and Levine, 2000;Kim et al, 2011;Chung, 2012). These findings indicate that GbNRX1 functions as an important regulator of apoplastic ROS homeostasis after its rapid production in cotton in response to V. dahliae invasion.…”
Section: Gbnrx1 Is An Important Regulator Of Apoplastic Ros Homeostasismentioning
confidence: 86%
“…The other cellular responses observed in bioautographs viz. inhibition of mycelial growth and early sporulation around the inhibition zone may be attributed to the induction and cross interaction between different signalling pathways viz "two component" histidine kinase, HOG1-mitogen activated protein kinase and SKN7-mediated ROS detoxification in fungal strains, which play an important role in regulating sporulation and other metabolic events in fungi (Kuang-Ren Chung, 2012).…”
Section: Discussionmentioning
confidence: 99%